Modelling the effectiveness of PPP road infrastructure projects by applying random forests - Rudžianskaitė–Kvaraciejienė, Rūta; Apanavičienė, Rasa; Gelžinis, Adas (Journal of Civil Engineering and Management, 2015)
Transport sector is very important for development of local economies, so it is intensively studied in different countries. Road infrastructure construction projects in many European countries are mainly carried out through various forms of Public–Private Partnership (PPP). Financial evaluation, private partner selection criteria, technical characteristics and very important focus of sustainable development components (environmental, social and economic) of PPP road infrastructure development projects are widely analysed in the scientific literature. Although many research studies were published for PPP road infrastructure projects efficiency assessment from different aspects, there have not been created assessment methodology with all key areas incorporated altogether. The authors provide an integrated PPP road infrastructure projects effectiveness modelling methodology by applying Random Forest technique. The developed methodology is recommended to be applied for PPP road infrastructure projects effectiveness prediction from the private and public sector perspectives.